Structural insights into catalytical capability for CPT11 hydrolysis and substrate specificity of a novel marine microbial carboxylesterase, E93 - Li, Yang; Rong, Zhen; Li, Zhengyang; Cui, Henglin; Li, Jixi; Xu, Xue-Wei (Frontiers in Microbiology, 2023)
CPT11 (Irinotecan; 7-ethyl-10-[4-(1-piperidino)-1-piperidino] carbonyloxycamptothecin) is an important camptothecin-based broad-spectrum anticancer prodrug. The activation of its warhead, SN38 (7-ethyl-10-hydroxycamptothecin), requires hydrolysis by carboxylesterases. NPC (7-ethyl-10-[4-amino-1-piperidinyl]-carbonyloxycamptothecin) is a metabolic derivative of CPT11 and is difficult to be hydrolyzed by human carboxylesterase. Microbial carboxylesterase with capability on NPC hydrolysis is rarely reported. The substrate-enzyme interaction between NPC and the enzyme is not clear. A carboxylesterase, E93, which was identified from a marine bacterium, can hydrolyze both CPT11 and NPC. The high-resolution structure (1.77Å) was resolved and molecular docking was adopted to analyze the interaction of E93 with p-NP (p-nitrophenyl), CPT11, and NPC substrates. Three core regions (Region A, B, and C) of the catalytic pocket were identified and their functions on substrates specificity were validated via mutagenesis assays. The Region A was involved in the binding with the alcohol group of all tested substrates. The size and hydrophobicity of the pocket determined the binding affinity to the three substrates. The Region B accommodated the acyl group of p-NP and CPT11 substrates. The polarity of this region determined the catalytic preference to both substrates. The Region C specifically accommodated the acyl group of NPC. The interaction from the acidic residue, E428, contributed to the binding of E93 with NPC. The study analyzed both unique and conserved structures of the pocket in E93, for the first time demonstrating the discrepancy of substrate-enzyme interaction between CPT11 and NPC. It also expanded the knowledge about the substrate specificity and potential application of microbial Family VII carboxylesterases.